2020
DOI: 10.1038/s41598-020-69137-1
|View full text |Cite
|
Sign up to set email alerts
|

Identification of sequence polymorphisms at 58 STRs and 94 iiSNPs in a Tibetan population using massively parallel sequencing

Abstract: Massively parallel sequencing (MPS) has rapidly become a promising method for forensic DNA typing, due to its ability to detect a large number of markers and samples simultaneously in a single reaction, and sequence information can be obtained directly. In the present study, two kinds of forensic genetic markers, short tandem repeat (STR) and identity-informative single nucleotide polymorphism (iiSNP) were analyzed simultaneously using ForenSeq DNA Signature Prep Kit, a commercially available kit on MPS platfo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
15
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 53 publications
4
15
2
Order By: Relevance
“…The number of different alleles found here (528 different STR alleles) was higher than those reported in Spanish French [4], Asian [5], and Peruvian [6] populations. Also, our RSB results improve importantly the combined PD and CE compared with those previously obtained in Monterrey City but based on 23 aSTRs genotyped by CE [19].…”
Section: Discussioncontrasting
confidence: 82%
See 2 more Smart Citations
“…The number of different alleles found here (528 different STR alleles) was higher than those reported in Spanish French [4], Asian [5], and Peruvian [6] populations. Also, our RSB results improve importantly the combined PD and CE compared with those previously obtained in Monterrey City but based on 23 aSTRs genotyped by CE [19].…”
Section: Discussioncontrasting
confidence: 82%
“…These results may be caused by sampling errors, especially when it comes from a cosmopolitan population such as Monterrey City, the second-most-important metropolis in Mexico. Although a larger population sample size could exhibit more allele diversity, producing more accurate estimates, we were able to observe as far as 367 different aSTR alleles, which is similar or superior to previous studies with the DPS-A of the ForenSeq™ DNA Signature Prep [3][4][5].…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…Among the 653 unique sequence‐based alleles (including the flanking region) observed in this study, 35 identified in 25 loci (12 A‐STRs loci, 11 Y‐STR loci, and 2 X‐STRs loci, respectively) were not recorded in the STR Sequencing Project (Gettings et al, 2017) and have never been reported in any of the previous studies (Barrio et al, 2019; Churchill et al, 2017; Delest et al, 2020; Devesse et al, 2018, 2020; Gettings et al, 2015, 2016; Hussing et al, 2019; Jäger et al, 2017; Khubrani et al, 2019; Kim et al, 2016, 2018; Novroski et al, 2016; Peng et al, 2020; Phillips, Devesse, et al, 2018; Phillips, Gettings, et al, 2018; Wang et al, 2020; Wendt et al, 2017). Sanger sequencing was performed to verify these novel sequence‐based alleles (data not provided) and all 35 are listed in Table 2.…”
Section: Resultsmentioning
confidence: 84%
“…X-STRs and Y-STRs were not considered for the PI calculation since little effective information could be obtained for cases presented in this study. As there is no significant LD in the Chinese population for these iiSNPs and A-STRs after Bonferroni correction [22,32], the PI values of iiSNPs and A-STRs were multiplied to calculate the CPI values. When combining the SNP and A-STR marker, 82.35% (14/17), 88.24% (15/17), 94.12% (16/17) and 94.12% (16/17) of real family cases could be accurately determined with an LR threshold for inclusion set as 10,000, 1000, 100 and 10, respectively (Table 3).…”
Section: Cpis With Snp and Str Typing For Nipptmentioning
confidence: 99%